TUNTUTAN PROVISI DALAM GUGATAN PELANGGARAN MEREK PADA PENGADILAN NIAGA - Devi Marlita Martana (University of Udayana, 2013)
Act Number 15 Year 2001 regarding Trademark has set the provisional charges. Provisional charges may be filed by the plaintiff while the investigation process of trademark infringement lawsuit in court of commerce is still ongoing. In a civil proceeding, the provisional charge must not be the primary charge, however the provisional charge that is set out in the Trademark Act has already concerned the primary charge. Actions that can be requested in the provisional charge according to Article 78 paragraph (1) in the Trademark Act include cessation of production, cessation of circulation of goods and / or services using Plaintiff's trademark illegally. Using literature study that utilizes primary legal materials and secondary legal materials as the research object, the results of the discussion are expected to be based on sufficient arguments to provide benefits for those who are interested to learn the trademark law enforcement.